Risk factors for high-altitude headache upon acute high-altitude exposure at 3700 m in young Chinese men: a cohort study - Bian, Shi-Zhu; Zhang, Ji-Hang; Gao, Xu-Bin; Li, Ming; Yu, Jie; Liu, Xi; Dong, Jun-Qing; Chen, Guo-Zhu; Huang, Lan (Journal of headache and pain, 2013)
Background This prospective and observational study aimed to identify demographic, physiological and psychological risk factors associated with high-altitude headache (HAH) upon acute high-altitude exposure. Methods Eight hundred fifty subjects ascended by plane to 3700 m above Chengdu (500 m) over a period of two hours. Structured Case Report Form (CRF) questionnaires were used to record demographic information, physiological examinations, psychological scale, and symptoms including headache and insomnia a week before ascending and within 24 hours after arrival at 3700 m. Binary logistic regression models were used to analyze the risk factors for HAH. Results The incidence of HAH was 73.3%. Age ( p =0.011), physical labor intensity (PLI) ( p =0.044), primary headache history ( p <0.001), insomnia ( p <0.001), arterial oxygen saturation (SaO 2 ) ( p =0.001), heart rate (HR) ( p =0.002), the Self-Rating Anxiety Scale (SAS) ( p <0.001), and the Epworth Sleepiness Scale (ESS) ( p <0.001) were significantly different between HAH and non-HAH groups. Logistic regression models identified primary headache history, insomnia, low SaO 2 , high HR and SAS as independent risk factors for HAH. Conclusions Insomnia, primary headache history, low SaO 2 , high HR, and high SAS score are the risk factors for HAH. Our findings will provide novel avenues for the study, prevention and treatment of HAH.